Physics of wire array Z-pinch implosions: Experiments on magpie generator - Lebedev,SV; Aliaga-Rossel,R; Bland,SN; Chittenden,JP; Dangor,AE; MGHaines (1999)
The study of the plasma behaviour during different stages of the wire array z-pinch implosions was investigated. Experiments were performed on the MAGPIE generator with a current rising to 1.4MA in 240ns. Time-resolved soft X-ray images were obtained with a gated 4-frame camera. Comparison of the instabilities in different wires shows that they are not correlated during the initial stages of the discharge. The scaling of the time of appearance of the global instability with the number of wires was found to be consistent with a heuristic model for the magnetic rayleigh-taylor instability whose initial perturbation amplitude was determined by statistically averaging the initial uncorrelated instabilities of the individual wires.